Caspase-11 signaling promotes damage to hippocampal CA3 to enhance cognitive dysfunction in infection - Ni Liang; Yi Li; Chuang Yuan; Xiaoli Zhong; Yanliang Yang; Fang Liang; Kai Zhao; Fangfang Yuan; Jian Shi; Erhua Wang; Yanjun Zhong; Guixiang Tian; et al. (BMC, 2024)
Abstract Background Cognitive dysfunction caused by infection frequently emerges as a complication in sepsis survivor patients. However, a comprehensive understanding of its pathogenesis remains elusive. Methods In our in vivo experiments, an animal model of endotoxemia was employed, utilizing the Novel Object Recognition Test and Morris Water Maze Test to assess cognitive function. Various techniques, including immunofluorescent staining, Western blotting, blood‒brain barrier permeability assessment, Limulus Amebocyte Lysate (LAL) assay, and Proximity-ligation assay, were employed to identify brain pathological injury and neuroinflammation. To discern the role of Caspase-11 (Casp11) in hematopoietic or non-hematopoietic cells in endotoxemia-induced cognitive decline, bone marrow chimeras were generated through bone marrow transplantation (BMT) using wild-type (WT) and Casp11-deficient mice. In vitro studies involved treating BV2 cells with E. coli-derived outer membrane vesicles to mimic in vivo conditions. Results Our findings indicate that the deficiency of Casp11-GSDMD signaling pathways reverses infection-induced cognitive dysfunction. Moreover, cognitive dysfunction can be ameliorated by blocking the IL-1 effect. Mechanistically, the absence of Casp11 signaling significantly mitigated blood‒brain barrier leakage, microglial activation, and synaptic damage in the hippocampal CA3 region, ultimately leading to improved cognitive function. Conclusion This study unveils the crucial contribution of Casp11 and GSDMD to cognitive impairments and spatial memory loss in a murine sepsis model. Targeting Casp11 signaling emerges as a promising strategy for preventing or treating cognitive dysfunction in patients with severe infections.